An Interview with Marcia Tate: Formative Assessment and Brain Based Learning - Michael Shaughnessy (Intelektual Pustaka Media Utama, 2016)
In this interview, Dr. Marcia Tate discusses her work and focuses on critical issues in brain based learning, and the need for both formative and summative assessment. Tangential issues such as grade retention, and response to intervention are also discussed. It is hope that this interview will assist teachers in the instructional and learning process and aid in both formative and summative assessment.